KONSTRUKSI TINDAK PIDANA PEMBUNUHAN ANTARA DELIK PEMBUNUHAN BIASA (PASAL 338 KUHP) DENGAN DELIK PEMBUNUHAN BERENCANA - Simaremare, Yoseanna Anastasya; Mulyadi, Mahmud; Trisna, Wessy (Smart Education, 2025)
Abstract: This article analyzes the construction of criminal acts of murder, comparing ordinary murder (Article 338 of the Criminal Code) with premeditated murder (Article 340 of the Criminal Code), using the Ferdy Sambo case study (Decisions No.796/Pid.B/2022/PN Jkt.Sel, No.53/Pid/2023/PT DKI, and 813 K/Pid/ 2023). Criminal law imposes varied penalties; unpremeditated murder faces 15 years, while premeditated murder can result in death, life imprisonment, or 20 years. The Ferdy Sambo case, involving the murder of Brigadier YS on July 8, 2022, was charged under Article 340 of the Criminal Code. This research uses a normative descriptive analytical method. Ferdy Sambo was sentenced to death by the District Court and High Court, but the Supreme Court's cassation revised it to life imprisonment due to a dissenting opinion. Analysis shows the Judges inadequately considered subjective elements and lacked psychological expert opinion to assess the perpetrator's mental state for the